Pertanggungjawaban Pidana Korporasi Dalam Tindak Pidana Di Bidang Perbankan - H. Nurianto RS (Universitas Mahendradatta, 2018)
The study on “Corporate Liability in Banking Criminal” aims to knowand give in-depth description concerning corporate liability of banking crime andlegal protection of banking criminal as a corporate. This study deals with normative law with analytical and conceptual approach,statute approach, and policy-oriented approach.The legal material in this study was obtained from primary and secondary source.The technique for collecting legal material is a combination of snowball andsystematic method while the study was analyzed by means of descriptiveevaluative, interpretative, comparative, and argumentative analysis.The findings show that there are no provisions of Banking Law that expressly statecorporation as legal subject. Although Article 46 Law No. 7, 1772 replaced by LawNo. 10, 1998 expilicitly states that a corporate as legal subject but there are noprovisions stating that a corporate can be made responsible criminally.Legal protection fror the victim in criminal law only gives abstract protection(indirect protection). Althogh in the legislation of criminal law as in the provisionof Article 14 c of the Criminal Code, Law No. 7, 1955 and also law No. 8, 1981contain provision of victim protection, but this provision is facultative in nature.While the legal protection of a victim in Law No. 8 is Hard to put into practice. Thelegal protection of a victim in the banking area as a corporate has a number ofabstacles. These obstacles indeed have some influence in upholding Law No. 7,1992 which has beeb changed into Law No. 10, 1998 about banking so that theimplications that emerges and legas protections of criminal victim in the bankingarea are still weak.